Dominant Paragraph Errors Made By The Students In Writing Essay (Jurnal Keguruan dan Ilmu Pendidikan, 2018)
Paragraph is a part of essay. The paragraphs in the essay divided into three parts, they are introductory paragraph, body or supporting paragraph and concluding paragraph. In the introductory paragraph there is a thesis statement. Thesis statement is a main idea of the whole paragraph in body or supporting paragraph. Body or supporting paragraph contains at least one paragraph. The paragraph in body should support the thesis statement in the introductory paragraph. And the concluding paragraph is a paragraph that can retell the thesis statement by using another sentence. To make essay we need paragraph. Because, the paragraph in the essay consists of three parts that is why this research only focused on analyzing the body or supporting paragraphs of the essay written by the students of English department of FKIP UKI Toraja.